An always convergent algorithm for the largest eigenvalue of an irreducible nonnegative tensor - Liu, Y.; Zhou, Guanglu; Ibrahim, Nur Fadhilah (Elsevier, 2010)
In this paper we propose an iterative method to calculate the largest eigenvalue of a nonnegative tensor. We prove this method converges for any irreducible nonnegative tensor. We also apply this method to study the positive definiteness of a multivariate form.